New and Safe Treatment of Food Impacted in the Esophagus: A Single Center Experience of 100 Consecutive Cases - Muhammad Shafique; Sheraz Yaqub; Erik S. Lie; Vegard Dahl; Frode Olsbø; Ola Røkke (Gastroenterology Research and Practice)
Aim. Large food bits can get stuck in the esophagus and must be removed by endoscopy. In some cases, this can be difficult or unsafe. We describe a new and safe treatment for such patients. Materials and Methods. 100 consecutive patients were referred to Akershus University Hospital with impacted food in the esophagus. In 36 patients (36%), the food passed spontaneously. In 59 (92%) of the remaining 64 patients, the food was removed by endoscopic intervention. In the last five patients, endoscopic removal was judged difficult or unsafe. These patients received the new treatment: one capsule Creon 10000 IU dissolved in 30 mL of Coca-Cola administered by a nasooesophageal tube four times daily for 2-3 days. Results. Of the 59 patients treated with endoscopic procedure, complications occurred in four (7%): three bleedings and one perforation of the esophagus. In five patients treated with Coca-Cola and Creon, the food had either passed or was soft after 2-3 days and could easily be removed. Conclusion. The treatment of choice of impacted food in the esophagus is endoscopic removal. In cases where this is difficult, we recommend treatment with Coca-Cola and Creon for 2-3 days before complications occur.